2017
DOI: 10.1097/ccm.0000000000002465
|View full text |Cite
|
Sign up to set email alerts
|

The New MIRUS System for Short-Term Sedation in Postsurgical ICU Patients*

Abstract: The MIRUS system is a promising and safe alternative for short-term sedation with sevoflurane of ICU patients. Atmospheric pollution is largely below the recommended thresholds (< 5 parts per million). Studies extended to more heterogeneous population of patients undergoing longer duration of sedation are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Measurements were taken 15 cm up from the MIRUS™ system and 15 cm from the reflector. These authors found that the mean SEVO concentrations were 0.15‐0.17 ppm, which were very similar to our results during baseline measurements and similar to pollution values using ISO and DES …”
Section: Discussionsupporting
confidence: 91%
“…Measurements were taken 15 cm up from the MIRUS™ system and 15 cm from the reflector. These authors found that the mean SEVO concentrations were 0.15‐0.17 ppm, which were very similar to our results during baseline measurements and similar to pollution values using ISO and DES …”
Section: Discussionsupporting
confidence: 91%
“…ISO, the cheapest VA, costs 0.39 € h −1 ; propofol, in comparison, about 0.41 € h −1 for an infusion rate of 3 mg kg −1 h −1 . Although comparable studies are rare, Romagnoli and colleagues reported nearly identical results for SEVO of approximately 8 ml for a slightly lower MAC of 0.45 [17]. Another observation, a case report of an obese woman suffering from acute respiratory distress syndrome after aspiration of gastric contents, demonstrated a twofold higher VA consumption of 53 ml h −1 DES to reach a fraction of 3.3–3.8% (3.21% in this study) [18].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, devices to reduce atmospheric VA pollution must be considered. Studies have shown that an air-conditioning with at least six air changes per hour and a scavenging system should be used to reach mean VA concentrations below 1 ppm in the patient room (the National Institute of Occupational Safety and Health has defined an exposure limit of 2 ppm for ISO, SEVO, and DES in the air) [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Sedation delivery, clinical and EEG-based depth assessment MIRUS™ (TIM, Koblenz, Germany) delivered inhalational sedation by employing an inhalational anaesthetic re ector, which features a controller to maintain the age-adjusted MAC pre-set target, regardless of changes in ow and minute-ventilation (9,10). The device continuously recorded the concentration of iso urane, sevo urane, or des urane.…”
Section: Randomizationmentioning
confidence: 99%